Evaluation of the dissemination of new Banana (Musa spp.) Technologies in Central Ghana - the role of technology characteristics - Dzomeku, B.M.; Staver, Charles; Aflakpui, G.K.S.; Sanogo, D.; Garming, H.; Ankomah, A.A.; Darkey, S.K. (International Society for Horticultural Science, 2010)
This study was conducted in the two Assin districts of the Central region of Ghana to examine factors that influence the adoption of new banana (Musa spp.) hybrids and other production technologies and to assess the impact of these technologies on smallholder farmers’ livelihoods. One hundred thirty households, comprising of 100 farmers from five communities that participated in the technologies dissemination and 30 farmers from three non-participating communities, were selected randomly and interviewed using structured questionnaires. The majority of respondents in participating communities and a fairly large proportion of non-project participating farmers had adopted the new technologies (paring, row planting, pruning and clean seed production). Although all farmers continued to plant their traditional cultivars, the new cultivars were essential to them. All the non-project participating farmers acquired their planting materials from participating farmers, within and outside their communities. Extension services, project farmers and non-governmental organizations were distributing new cultivars. In villages, where farmer-based organizations are actively induced by the project, planting materials and knowledge were transferred to non-project participants as well. This suggests great potentials of adoption of the disseminated innovations in the project communities as well as in non-project areas in Central Ghana. Social networking is an important factor for technology diffusion and adoption. Hence, the formation of farmers’ organizations as a result of the project had yielded dividends to the community. Strengthening farmers’ organizations and social networks can therefore be an effective approach to ensure large dissemination and adoption of improved banana and plantain technologies in the study area.